Market power and the volatility of markups in the food value chain: The role of Italian cooperatives - Hyejin Lee; Johan F. M. Swinnen; Patrick Van Cayseele (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2021)
Agricultural cooperatives have often been promoted as a way to increase their market power and to obtain stability of profit against uncertainty. This paper estimates the firm-level markups and markup volatility to identify the countervailing market power of cooperatives in the Italian fruits and vegetable sector and the dairy sector. We use the firm-level data of Italian firms for the period 2007-2014. We find that, overall, there is a tradeoff in cooperatives' role between obtaining market power and stability. Farmer cooperatives in both sectors gain stability in their markups but their markups are lower, on average, than those for non-cooperatives. For processor cooperatives, the fruits and vegetable sector obtains more market power. This appears to arise from the product differentiation strategy of the processors cooperative.
Keywords: L44; Q13; D23; 330; Cooperatives; market power; firm-level markups; volatility